Peningkatan Kapasitas UMKM “Menuju UMKM Yang Bankable” - Dila Angraini; Erika Astriani Aprilia; Wiwit Setyawati (Abdimisi, 2022)
This community service is in collaboration with Balai Besar Perluasan Kesempatan Kerja (BBPKK) Bandung Barat. The purpose of carrying out PKM activities is to provide understanding and direction to BBPKK Bandung Barat assisted MSMEs about the importance of becoming bankable MSMEs so that they are ready to receive injections of funds from the Government or in proposing additional working capital for business scale development. The target audience for this PKM activity is business actors, especially MSMEs who have been assisted by BBPPK Bandung Barat and nationally because the event is held online so that it can be accessed from anywhere. The total number of participants is 62 people with the activity time being held on December 9, 2022. The methods used in this PKM are counseling or lectures, tutorials, discussions, and mentoring. The results of the PKM activities obtained data that there are still many participating MSMEs that have not yet recorded, administered and archived the legality of the company and its business financial transactions. So that many MSMEs have not been able to take advantage of financing facilities to increase working capital from the Bank. After participating in this activity the participants began to be disciplined in terms of recording both business financial records and recording business legality, as well as maintaining the banking track record towards bankable MSMEs.